Anti-N-methyl-D-aspartate Receptor Encephalitis after Herpes Simplex Virus Encephalitis - John J. Vaidya (Archives of Medicine and Health Sciences)
Encephalitis due to herpes simplex virus 1 (HSV1) has been described as a potential trigger for the development of anti-N-methyl-D-aspartate receptor (NMDAR) autoimmune encephalitis within few days to months. Here, we report one such case of anti-NMDAR encephalitis which was triggered by preceding HSV encephalitis. The patient had a history of headache and fever of 1–2-week duration, and cerebrospinal fluid and magnetic resonance imaging picture suggestive of HSV encephalitis. After 2 weeks of completion of 14-day course of acyclovir, he had symptoms of altered behavior, headache, and vomiting. The possibility of anti-N-methyl-D-aspartate (NMDA) encephalitis occurring after HSV encephalitis was considered. Serum for anti-NMDA antibody came positive, and he improved with treatment. A high index of suspicion and awareness of such a possibility can help in making the diagnosis and initiate early therapy.